Acute physiological and psychological responses during an incremental treadmill test wearing a new upper-body sports garment with elastomeric technology - Janicijevic, Danica; Saez-Berlanga, Angel; Babiloni-Lopez, Carlos; Martin-Rivera, Fernando; Jiménez-Martínez, Pablo; Silvestre-Herrero, Alejandro; Martínez-Puente, Javier; Ferradás-Nogueira, Pablo; Juesas, Alvaro; Gene-Morales, Javier; Chulvi-Medrano, Iván; Colado, Juan C. (Frontiers in Physiology, 2024)
Background: The use of elastomeric technology in sports garments is increasing in popularity; however, its specific impact on physiological and psychological variables is not fully understood. Thus, we aimed to analyze the physiological (muscle activation of the pectoralis major, triceps brachii, anterior deltoid, and rectus abdominis, capillary blood lactate, systolic and diastolic blood pressure, and heart rate) and psychological (global and respiratory rating of perceived exertion [RPE]) responses during an incremental treadmill test wearing a new sports garment for the upper body that incorporates elastomeric technology or a placebo garment. Methods: Eighteen physically active young adults participated in two randomized sessions, one wearing the elastomeric garment and the other wearing a placebo. Participants performed in both sessions the same treadmill incremental test (i.e., starting at 8km/h, an increase of 2 km/h each stage, stage duration of 3 min, and inclination of 1%; the test ended after completing the 18 km/h Stage or participant volitional exhaustion). The dependent variables were assessed before, during, and/or after the test. Nonparametric tests evaluated differences. Results: The elastomeric garment led to a greater muscle activation (p<0.05) in the pectoralis major at 16km/h (+33.35%, p=0.01, d=0.47) and 18km/h (+32.09%, p=0.02, d=0.55) and in the triceps brachii at 10km/h (+20.28%, p=0.01, d=0.41) and 12km/h: +34.95%, p=0.04, d=0.28). Additionally, lower lactate was observed at the end of the test (-7.81%, p=0.01, d=0.68) and after 5 min of recovery (-13.71%, p<0.001, d=1.00) with the elastomeric garment. Nonsignificant differences between the garments were encountered in the time to exhaustion, cardiovascular responses, or ratings of perceived exertion. Conclusion: These findings suggest that elastomeric garments enhance physiological responses (muscle activation and blood lactate) during an incremental treadmill test without impairing physical performance or effort perception.